BEHAVIOURAL INTERACTIONS BETWEEN THE ENDANGERED NATIVE FISH SARAMUGO, ANAECYPRIS HISPANICA, AND THE INVASIVE BLEAK, ALBURNUS ALBURNUS - Da Silva, J. (2019)
Invasive species have the potential to impact native fish through interference competition, which is especially concerning for the conservation of the valuable endemic ichtyofauna of the Iberian Peninsula. This study investigated the potential negative effect of the invasive bleak Alburnus alburnus on the behaviour of the critically endangered native Iberian saramugo Anaecypris hispanica.